The Influence of Leadership on the Transfer of Knowledge and Work Effectivity at Secretariat Office in Boven Digoel Regency - Yoseph Awunim; Abdul Rahman Kadir; Mahlia Muis (Magister Management, Hasanuddin University, 2020)
The research objective is to analyze the direct impact of leadership toward transfer knowledge and work effectiveness in Boven Digoel. Data analysis in this research is quantitative using a path analysis model (path analysis) with the help of Smart PLS Software version 3.2 .8. The research distributed questionnaires to 89 respondents of officers assigned at the secretariat office in Boven Digoel Regency. On the basis of statistical results, it was found that leadership can be said to have impacted positively and significant knowledge transfer and work effectiveness. The knowledge transfer also has a positive impact on work effectiveness.